2022
DOI: 10.34133/2022/9795675
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Crossover and Fast-Kinetics Thiolate Negolyte for Aqueous Redox Flow Batteries

Abstract: Aqueous redox flow batteries (ARFBs) are a promising technology for large-scale energy storage. Developing high-capacity and long-cycle negolyte materials is one of major challenges for practical ARFBs. Inorganic polysulfide is promising for ARFBs owing to its low cost and high solubility. However, it suffers from severe crossover resulting in low coulombic efficiency and limited lifespan. Organosulfides are more resistant to crossover than polysulfides owing to their bulky structures, but they suffer from slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The ultrathin PtRu NWs were synthesized via a colloidal chemistry approach by using platinum acetylacetonate (Pt(acac) 2 ) and ruthenium acetylacetonate (Ru(acac) 3 ) as the metal precursors, tungsten hexacarbonyl (W(CO) 6 ) and (1-hexadecyl) cetyltrimethylammonium bromide (CTAB) as the structure-directing agents, and oleylamine as the solvent. The mixture was then heated to 220 °C for 5 h in an oil bath.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrathin PtRu NWs were synthesized via a colloidal chemistry approach by using platinum acetylacetonate (Pt(acac) 2 ) and ruthenium acetylacetonate (Ru(acac) 3 ) as the metal precursors, tungsten hexacarbonyl (W(CO) 6 ) and (1-hexadecyl) cetyltrimethylammonium bromide (CTAB) as the structure-directing agents, and oleylamine as the solvent. The mixture was then heated to 220 °C for 5 h in an oil bath.…”
Section: Resultsmentioning
confidence: 99%
“…The development of environment-friendly and sustainable energy technologies is critical for the comprehensive transformation of energy structure from fossil fuels to renewable energy sources in the future [1][2][3][4][5][6][7][8]. Direct liquid fuel cells (DLFCs) technology provides a promising strategy to convert chemical energy into electric power [9].…”
Section: Introductionmentioning
confidence: 99%
“…Relatively, Wang et al reported a thiolate negolyte prepared by an exchange reaction between a polysulfide and an organosulfide, preserving the low crossover rate of the organosulfide and high reaction kinetics of the polysulfide. 89 Various PIRFBs of different positive and negative electrodes at a current density of 20 mA cm −2 under relatively similar operating conditions are summarized in Table 2. Fig.…”
Section: Polysulfide-halogen Redox Flow Batterymentioning
confidence: 99%
“…Aqueous Zn-ion batteries (ZIBs) have been considered as one of the promising energy storage systems for large-scale energy storage because of their high safety, low cost and environmental friendliness [1][2][3][4][5][6]. The development of aqueous ZIBs mainly focuses on the design of electrodes, optimization of electrolytes, and improvement of device configurations [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%